2008
DOI: 10.1128/jb.00562-07
|View full text |Cite
|
Sign up to set email alerts
|

Three Pathogenicity Islands of Vibrio cholerae Can Excise from the Chromosome and Form Circular Intermediates

Abstract: Vibrio pathogenicity island-2 (VPI-2) is a 57-kb region integrated at a transfer RNA (tRNA)-serine locus that encompasses VC1758 to VC1809 on the V. cholerae N16961 genome and is present in pandemic isolates. VPI-2 encodes a P4-like integrase, a restriction modification system, a Mu phage-like region, and a sialic acid metabolism region, as well as neuraminidase (VC1784), which is a glycosylhydrolase known to release sialic acid from sialoglycoconjugates to unmask GM1 gangliosides, the receptor for cholera tox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
127
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 103 publications
(133 citation statements)
references
References 38 publications
6
127
0
Order By: Relevance
“…The 12-kb insert did not show significant match with any sequences in the National Center for Biotechnology Information GenBank database, except for a 103-bp region with 78% sequence similarity to a transcriptional regulator of V. parahaemolyticus. Recent analyses of the VC1773 to VC1810 region of this island suggest this is a hot-spot for novel DNA insertion (58). The presence of virulence factors, including two reported in V. cholerae, namely pre-CTXΦ and VPI-2 in the noncholera Vibrio antiquarius from a deep-sea environment, suggests their multifaceted role outside the human host; that is, ecological function in the natural habitat and alternate evolutionary origins apart from their core genome.…”
Section: Resultsmentioning
confidence: 99%
“…The 12-kb insert did not show significant match with any sequences in the National Center for Biotechnology Information GenBank database, except for a 103-bp region with 78% sequence similarity to a transcriptional regulator of V. parahaemolyticus. Recent analyses of the VC1773 to VC1810 region of this island suggest this is a hot-spot for novel DNA insertion (58). The presence of virulence factors, including two reported in V. cholerae, namely pre-CTXΦ and VPI-2 in the noncholera Vibrio antiquarius from a deep-sea environment, suggests their multifaceted role outside the human host; that is, ecological function in the natural habitat and alternate evolutionary origins apart from their core genome.…”
Section: Resultsmentioning
confidence: 99%
“…Generation of amplicons with right and left junction primers suggests that VPIs have been integrated in the large chromosome of these isolates at sites identical to those of O1 strains (Fasano et al, 1991). Murphy & Boyd (2008) showed that all three pathogenicity islands can excise from the chromosome, which is likely a first step in their horizontal transfer. Boyd et al (2000) suggest that Vibrio mimicus may be a significant reservoir for VPI phage and may play an important role in the emergence of new toxigenic V. cholerae isolates.…”
Section: Ljf-vpir Aldaf-tagar Vpi2f-r Vpi3f-r Vpi4f-r Vpi5f-r Tcpif-qmentioning
confidence: 99%
“…The major virulence factors of V. cholerae, the aetiological agent of Asiatic cholera, are encoded by genes within A+T-rich horizontally transmissible genetic elements (Davis & Waldor, 2003;McLeod et al, 2005;Murphy & Boyd, 2008). These genes are regulated by several environmental signals to ensure that their products are expressed when the bacterium arrives at appropriate sites in the host and that they are repressed elsewhere (Lee et al, 1999;Schild et al, 2007).…”
Section: Opposing H-ns In Vibrio Choleraementioning
confidence: 99%